Human or Artificial? A Meta-Analysis of the Effects of AI-Driven Marketing Interactions on Consumer Trust, Purchase Intention, and Brand Engagement - Muchlis Abbas; Aditya Halim Perdana Kusuma Putra (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine AI-driven viral marketing strategy by explaining the role of micro-influencers, short-form video, and electronic word of mouth in shaping consumer purchase intention. The study uses a qualitative literature study approach by reviewing, classifying, and synthesizing relevant scholarly works on artificial intelligence in marketing, viral marketing, influencer credibility, short-form video engagement, e-WOM, and consumer behavior. The results indicate that AI-driven viral marketing is not merely a technology-based promotional tool, but an integrated strategic system that combines algorithmic personalization, social credibility, visual engagement, and peer-to-peer communication. Artificial intelligence strengthens marketing effectiveness through personalized targeting, predictive analysis, and content optimization. Micro-influencers enhance consumer trust through perceived authenticity, expertise, and relational closeness. Short-form video increases attention, emotional response, and content shareability, while electronic word of mouth provides social validation, reduces perceived risk, and strengthens purchase intention. The main finding of this study is that consumer purchase intention is shaped by the interaction between technological relevance and social trust. Therefore, effective viral marketing requires a balance between AI-based automation and human-centered communication. This study contributes theoretically by integrating AI marketing, influencer marketing, short-form video, and e-WOM into one conceptual framework, and managerially by offering strategic insights for designing credible and engaging digital marketing campaigns.